In vitro anticancer activity of curcumin loaded chitosan nanoparticles (CLCNPs) against Vero cells - Deepika; Minakshi Prasad; Arnav Salar; Raj Kumar Salar (Elsevier, 2022)
The global burden of cancer is rising due to increasing pollution, change in lifestyles and dietary habits rendering it as one of the leading cause of death worldwide. Poor availability of anticancer drugs in affected tissues necessitates higher doses and longer treatment regimens to treat most cancers. In the present investigation curcumin, an anticancer drug was loaded in chitosan nanoparticles by ionic gelation method and their anticancer effect was evaluated against the Vero cell line. The characteristics of nanoparticles were studied by UV-Vis spectroscopy, Fourier Transform Infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA), Differential thermal analysis (DTA), Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM). UV-Vis spectroscopy confirmed the synthesis of CLCNPs, whereas FTIR indicated different functional groups associated with the formation of these nanoparticles. TGA and DTA confirmed the stability of nanoparticles at high temperature. SEM revealed spherical shape of CLCNPs whereas TEM confirmed loading of curcumin in chitosan nanoparticles. The anticancer activity of CLCNPs was evaluated against Vero cell line in different concentrations (10, 20, and 50 µg) and it was observed that 50 µg concentration was most effective. CLCNPs can be used to treat cancer cells as curcumin is poorly soluble in aqueous solutions.